Poor livestock producers, the environment and the paradoxes of development policies - Pradère, Jean-Paul (OIE ParisFR, 2017)
Draws attention to the inequalities between countries and shows that the poorest countries do not have the capacity to tackle that challenge and to implement farm-sector policies to support the sustainable development of livestock farming.